How do you differentiate #V(x)=(2x^3+3)(x^4-2x)#?

Answer 1

#V'(x)=14x^6-4x^3-6#

Applying the rule of product

#(fg)'=f'g+fg'# we get #V'(x)=6x^2(x^4-2x)+(2x^3+3)(4x^3-2)#

Growing, we attain

#V'(x)=6x^6-12x^3+8x^6+12x^3-4x^3-6#
#V'(x)=14x^6-4x^3-6#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

#V'(x)=14x^6-4x^3-6#

#"differentiate using the "color(blue)"power rule"#
#•color(white)(x)d/dx(ax^n)=nax^(n-1)#
#"expand the factors using FOIL"#
#V(x)=2x^7-4x^4+3x^4-6x#
#color(white)(V(x))=2x^7-x^4-6x#
#V'(x)=14x^6-4x^3-6#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To differentiate the function ( V(x) = (2x^3 + 3)(x^4 - 2x) ), you would use the product rule of differentiation. Here's how you apply it:

  1. Identify the two functions being multiplied: ( f(x) = 2x^3 + 3 ) and ( g(x) = x^4 - 2x ).
  2. Apply the product rule: ( V'(x) = f'(x)g(x) + f(x)g'(x) ).
  3. Differentiate ( f(x) ) and ( g(x) ) separately.
  4. Substitute the derivatives and the original functions into the product rule formula.
  5. Simplify the expression to get the derivative of ( V(x) ).

Here's the step-by-step process:

  1. ( f(x) = 2x^3 + 3 ) and ( g(x) = x^4 - 2x ).
  2. ( f'(x) = 6x^2 ) and ( g'(x) = 4x^3 - 2 ).
  3. Product rule: ( V'(x) = (6x^2)(x^4 - 2x) + (2x^3 + 3)(4x^3 - 2) ).
  4. Expand and simplify: ( V'(x) = 6x^6 - 12x^3 + 8x^6 - 4x^3 + 12x^3 - 6 ).
  5. Combine like terms: ( V'(x) = 14x^6 - 16x^3 - 6 ).

So, the derivative of ( V(x) ) is ( V'(x) = 14x^6 - 16x^3 - 6 ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7